The Comparition of the Efficacy of Two Different Probiotics in Rotavirus Gastroenteritis in Children - Özlem Erdoğan; Bilge Tanyeri; Emel Torun; Erdem Gönüllü; Hüseyin Arslan; Ufuk Erenberk; Faruk Öktem (Journal of Tropical Medicine)
Objectives. The aim of the study is to compare the clinical effectiveness of the probiotics—Saccharomyces boulardii and Bifidobacterium lactis—in children who had been diagnosed with rotavirus gastroenteritis. Materials and methods. Seventy five patients aged between 5 months–5 years diagnosed as rotavirus gastroenteritis were included in the study. The patients diagnosed as rotavirus gastroenteritis by latex agglutination test in stool were divided into 3 groups of twenty-five patients each: First group was given oral rehydration therapy and rapid refeeding with a normal diet with Saccharomyces boulardii (spp. I-745), second group was given oral rehydration therapy and rapid refeeding with a normal diet with Bifidobacterium lactis (spp. B94, culture number:𝑁∘118529) and third group received only oral rehydration therapy and rapid refeeding with a normal diet. Results. The duration of diarrhea was shorter in the group given oral rehydration therapy and rapid refeeding with a normal diet with Bifidobacterium lactis and Saccharomyces boulardii than the group given only oral rehydration therapy and rapid refeeding with a normal diet. Conclusion. Bifidobacterium lactis has a complemental role in the treatment of rotavirus gatroenteritis and other probiotics may also have a beneficial effect in rotavirus gastroenteritis compared with the therapy included only oral rehydration therapy and rapid refeeding with a normal diet.